PARAREL PROSESING SEBAGAI METODE DALAM PENINGKATAN KINERJA CPU (CENTRAL PROSESING UNIT) , STUDI KASUS : KINERJA STEGANOGRAFI - Asmawati, Ari; Susanto, Fredy (Lembaga Marwah Rakyat, 2024)
Hardware or peripherals are providers of resources for computing. Hardware is objects that can be seen and touched. Software is a means that tells the hardware what to do. In contrast to hardware, software is something abstract. And it can only be seen from what it does to the hardware. Software is further divided into two parts, namely the operating system and application programs. The operating system is software that is responsible for controlling and coordinating the use of hardware for various applications for various users. Meanwhile, application programs are software that determines how resources are used to solve user problems. Then, brainware/user is a computer user. It can be a human, another machine, or another computer. In increasing the number of processes that can be completed in one unit of time (increased throughput). It should be remembered that this does not mean that the computing power increases by the number of processors. What increases is the amount of work that can be done in a certain time. So it is necessary to develop processor systems by sharing work in parallel. Keywords: multiprocessor, parallel, steganography.